Use of the Altman Z-Score Method to Predict Bankruptcy of Islamic Banks Listed on the Indonesia Stock Exchange - Tuti Mayang Faristina; Risma Apriyani (Indonesian Development of Economics and Administration Journal, 2023)
This study was conducted to predict the bankruptcy of Islamic banking listed on the Indonesia Stock Exchange from 2018 to 2022, using the Altman Z-score method. The number of banks studied were three banks namely Bank Syariah Indonesia, Tbk, Bank Aladin, and Bank BTPN Syariah, Tbk. The analysis technique in this study is the Altman Z-score method using 5 ratios, namely the ratio of working capital to total assets (X1), the ratio of retained earnings to total assets (X2), the ratio of earnings before interest and taxes to total assets (X3), ratio of market value of equity to total debt (X4) and total assets (X5) The formula for Altman’s Z-score method to calculate the soundness of a company is Z= 1.2X1 + 1.4X2 + 3.3X3 + 0.6X4 + 1.0X5 . Z-Score indicators to determine bankruptcy of companies are collected into healthy categories (Z-score > 2.99), gray area (Z-score between 1.81 and 2.99) and bankrupt (Z-score < 1.81). After making a complaint that Islamic banks are listed on the Indonesia Stock Exchange from 2018 to 2022, they score various Z-Score values of 2,784, 3,957 and 5,291 or in other words the 3 banks are indicated to be healthy and there are banks which are indicated to be prone to bankruptcy.